Comparison of executive functions in individuals with high and low levels of schizotypal trait - Abbasi Sarajehlou, Saeid; Khajeh, Somayeh; Masrour, Cheeman; Azizi, Morteza (Frontiers in Psychology, 2023)
The dimensional approach to Schizotypal Personality Disorder (SPD) indicates that SPD includes a constellation of maladaptive personality traits on a continuum with general personality functioning. This study aimed to compare executive functions (EFs) in low and high-level schizotypal individuals. Using a convenient sampling method, we recruited 120 individuals, from which 30 individuals with high schizotypal trait levels (fourth quartile) and 30 participants with lower schizotypal trait levels (first quartile) were selected based on their scores on the schizotypal personality disorder questionnaire. Then, participants from the two groups were administered the Corsi Block-Tapping Test (CBTT), Wisconsin Card Sorting Test (WCST), and Continuance Performance Test (CPT). The results indicated individuals with higher schizotypy trait levels performed significantly poorer in tasks measuring working-visual-spatial memory, cognitive flexibility, sustained attention, and response inhibition. This pattern of results indicated that EF dysfunctions in individuals with higher schizotypy trait levels would cause significant disturbances in multiple areas of life. The practical implications of the findings are further discussed.